2019
DOI: 10.1016/j.vetimm.2018.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects and immune responses of probiotic treatment in ruminants

Abstract: Gut microbial colonization and establishment are vital to ruminant health and production. This review article focuses on current knowledge and methods used to understand and manipulate the gut microbial community in ruminant animals, with a special focus on probiotics treatment. This review highlights the most promising of studies in this area, including gut microbial colonization and establishment, effect of gastrointestinal tract microbial community on host mucosal innate immune function, impact of feeding s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 129 publications
1
24
0
1
Order By: Relevance
“…The probiotic and prebiotic substances contained in the feed ration of the experimental group demonstrably increased the live weight gain. A number of studies are described which report the positive effect of the use of probiotic feed supplements on the health and live weight gain of calves (Zhang et al, 2016;Raabis et al, 2019;Renaud et al, 2019). These results agree with the findings of Timmerman et al (2005) and Frizzo et al (2010).…”
Section: Resultssupporting
confidence: 74%
“…The probiotic and prebiotic substances contained in the feed ration of the experimental group demonstrably increased the live weight gain. A number of studies are described which report the positive effect of the use of probiotic feed supplements on the health and live weight gain of calves (Zhang et al, 2016;Raabis et al, 2019;Renaud et al, 2019). These results agree with the findings of Timmerman et al (2005) and Frizzo et al (2010).…”
Section: Resultssupporting
confidence: 74%
“…The mechanism that LAC can regulate the oxidative stress of animals may be related to modulation of nuclear factor erythroid-2-related factor 2 (Nrf2) signals and suppression of nuclear factor kappa-B (NF-kB) inflammatory pathway [30]. Moreover, it has been reported that Lactobacillus plays a significant role in regulating gastrointestinal mucosal immune cells and maintaining a healthy gastrointestinal tract [31]. Lactobacillus can produce bactericidal substances and compete for the attachment plaque with pathogens and toxins [31].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been reported that Lactobacillus plays a significant role in regulating gastrointestinal mucosal immune cells and maintaining a healthy gastrointestinal tract [31]. Lactobacillus can produce bactericidal substances and compete for the attachment plaque with pathogens and toxins [31].…”
Section: Discussionmentioning
confidence: 99%
“…Dependiendo del tipo de proteína, cierta cantidad es degradada por la acción de la microflora ruminal, mientras que la fracción no degradable, constituye la proteína de sobrepaso. El NNP es de gran solubilidad y completamente hidrolizado en el rumen y transformado a amoníaco, siempre y cuando no rebase la capacidad de la microflora ruminal de convertir más NNP en proteína microbial (Raabis, S., & Cersosimo, 2019), el objetivo final de este metabolismo es proporcionar aminoácidos al organismo para que puedan ser aprovechados eficazmente en las diferentes funciones.…”
unclassified